CAREER DEVELOPMENT, MENTORING QUALITY, AND EMPLOYEE RETENTION AMONG GENERATION Z WORKERS: MEDIATING ROLE OF ORGANIZATIONAL COMMITMENT - Fatwa Zuhaena (Jurnal Akuntansi dan Pajak, 2022)
Generation Z employees (born 1997–2012) present unprecedented retention challenges for organizations due to their distinctly higher turnover propensity and career development expectations compared to prior generations. This study investigates the effects of career development and mentoring quality on employee retention among Generation Z workers in the banking and financial services sector in Purwokerto, Central Java, with organizational commitment as a mediating variable. Anchored in Social Exchange Theory (Blau, 1964) and Career Construction Theory (Savickas, 2005), five hypotheses were tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) with a sample of 148 Generation Z employees from eight banking institutions in Purwokerto. Results indicate that career development (β = 0.341, p < 0.001) and mentoring quality (β = 0.298, p < 0.01) both positively affect organizational commitment; organizational commitment strongly predicts retention (β = 0.412, p < 0.001); and organizational commitment significantly mediates the career development-retention (indirect β = 0.140, p < 0.01) and mentoring-retention (indirect β = 0.123, p < 0.01) relationships. The model explains 59.7% of retention variance (R² = 0.597). Findings provide actionable retention strategies for HR practitioners managing Generation Z talent in Indonesian financial services. Keywords: career development; mentoring quality; employee retention; Generation Z; organizational commitment; banking sector; Social Exchange Theory